2013
DOI: 10.1080/08997764.2013.785552
|View full text |Cite
|
Sign up to set email alerts
|

Attracted but Unsatisfied: The Effects of Sensational Content on Television Consumption Choices

Abstract: This paper investigates experimentally the effects of sensational content on viewing choices and satisfaction in television consumption. We find that the presence of verbal violence in one program causes subjects to watch more of that program. However, subjects do not experience higher satisfaction with the program. In addition, they report lower satisfaction with the overall viewing experience. These findings are robust to the use of different program types for the experimental manipulation. Overall, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…Previous research has investigated the direct and indirect effects of sensational news on viewer attitudes, attention, beliefs, trust, and satisfaction with the news (Burgers & de Graaf, 2013; Hendriks Vettehen et al, 2008). Consistent with a previous study that found that sensational content enhanced selective exposure (Stanca et al, 2013), our findings showed that online news platform users were more likely to click sensational news headlines containing alarm-related words. This offers empirical support for the selectivity paradigm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous research has investigated the direct and indirect effects of sensational news on viewer attitudes, attention, beliefs, trust, and satisfaction with the news (Burgers & de Graaf, 2013; Hendriks Vettehen et al, 2008). Consistent with a previous study that found that sensational content enhanced selective exposure (Stanca et al, 2013), our findings showed that online news platform users were more likely to click sensational news headlines containing alarm-related words. This offers empirical support for the selectivity paradigm.…”
Section: Discussionsupporting
confidence: 92%
“…The sensational news alarm system model that explains the environmental surveillance need is supported by a few empirical studies. Sensational content potentiates selective exposure (Stanca, Gui, & Gallucci, 2013). For example, sensational television news, such as stories about death, disasters, riots, fires, and terrorism, moderately enhance the emotional arousal of viewers, which in turn attracts their attention to like these television news stories (Hendriks Vettehen et al, 2008).…”
Section: Evolutionary Needs: a Uses And Gratifications Approachmentioning
confidence: 99%
“…It is also worth noting that spending time on news is not a stamp of approval from users. Previous research showed that people consume news that they do not see as quality news (Costera Meijer 2007), news that does not lead to a satisfying viewing experience (Stanca, Gui, and Gallucci 2013), and news that they do not trust (Tsfati and Cappella 2003). Similarly, our participants had no problem admitting that their attention to news did not correspond with their judgement of quality.…”
Section: Resultsmentioning
confidence: 50%
“…. The distinction between attraction and satisfaction found in earlier research (e.g., Costera Meijer 2007;Stanca et al 2013) came up repeatedly in the DS interviews. Multiple viewers argued that DS tends to report about politicians or people in powerful positions in a suggestive manner.…”
Section: Eenvandaag (Daily Current Affairs Show Ds)mentioning
confidence: 51%
“…Trussler and Soroka (2014) found that people’s stated (dis)preference for negative or horse-race news did not predict their selection of news stories, whereas Lang et al (2005) found that viewers’ evaluations of newscasts did not predict which news they watched. Stanca et al (2013) found that although sensational content (“verbal violence”) in political talk shows led to longer viewing time, it also led to a less satisfactory overall viewing experience. Grabe et al (2003) and Grabe et al (2000) even found a difference between people’s bodily and affective reactions to news with a “tabloid” production (e.g., sound effects, music, flash frames): It increased physiological measures of attention and arousal, but had, respectively, no significant effect or a negative effect on self-reported interest or enjoyment, and a negative effect on objectivity and believability.…”
Section: Literature Reviewmentioning
confidence: 98%